2022
DOI: 10.17309/tmfv.2022.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Justification of the Selection Techniques in Martial Arts using Wald's Sequential Analysis

Abstract: The study purpose was to develop a selection technique in martial arts based on indices of physical development using Wald's sequential analysis. Materials and methods. 12 anthropometric indicators were determined. 9 indexes of physical development were calculated on their basis. 16 elite athletes (candidates for masters and masters of sports) were divided into two groups. Group 1 included 7 athletes (judo, sambo, Greco-Roman and freestyle wrestling) aged 18.43±0.43. Group 2 included 9 kickboxing athlete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The proportion of such athletes in group 1 was (83.33±9.52)%, in group 2 -(73.33±11.42)%. Available studies have confirmed that in elite kickboxing athletes this index reflects a fairly high level of torso muscle development [10,28]. In our opinion, the results obtained should be assessed as a trend towards an increase in this index due to regular training.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The proportion of such athletes in group 1 was (83.33±9.52)%, in group 2 -(73.33±11.42)%. Available studies have confirmed that in elite kickboxing athletes this index reflects a fairly high level of torso muscle development [10,28]. In our opinion, the results obtained should be assessed as a trend towards an increase in this index due to regular training.…”
Section: Discussionsupporting
confidence: 51%
“…The choice of a battery of methods is determined by the available literature data. In the article [28], a similar battery of indices was used to develop a selection technique for martial arts (kickboxing or wrestling). The use of Wald's sequential analysis made it possible to develop a simple and accessible Notes.…”
Section: Discussionmentioning
confidence: 99%